KONSEP AL-DARURAH TUQADDAR BIQADARIHA DALAM INOVASI PAKAIAN BERSALIN DARI PERSPEKTIF MAQASID AL-SYARIAH: The Concept of al-Darurah Tuqaddar Biqadariha in the Maternity Garment Innovation from the Perspective of Maqasid al-Shariah - Ismail, Siti Khatijah; Ahmad, Ridzwan; Khalid, Khairul Afnan (Jurnal Syariah, 2017)
Birth management and procedures require that the private parts (‘awrat) of women be exposed in special circumstances. This is permitted via the concept of al-darurah tuqaddar biqadariha. Thus far, modern medical practices have been adopted by the Ministry of Health (MOH) in their general documents and manuals with respect to the dignity and privacy of patients. However, the absence of such standards with regards to ‘awrat has caused discomfort among female patients in labor and feel that their privacy is not being safeguarded. Recognizing the needs and demands of society and women in particular, an innovative product has been introduced in the form of ‘maternity pants’. The design of the pants, which aims to fulfill the need to safeguard the female genitalia from being exposed unneccesarily, should be analyzed in terms of whether it is or is not they are Maqasid al-Shari‘ah compliant. Therefore, the purpose of this study is to observe whether the design of these pants has met the demands of al-darurah tuqaddar biqadariha; or protecting the female private parts from being visible during childbirth. The results, based on product observation and interviews with medical practitioners, show that the product has indeed met the standard and is in line with the concept of ma la yudrak al-kull la yutraku kull.